Design and Simulation of an RF-MEMS Switch and analysis of its Electromagnetic aspect in realtion to stress - Amna Riaz; Muhammad Umair Javed Ilam Sindhu; Tahir Zaidi (Advances in Science, Technology and Engineering Systems Journal, 2018)
Microelectromechanical Systems (MEMS) are devices made up of several electrical and mechanical components. They consist of mechanical functions (sensing, thermal, inertial) and electrical functions (switching, decision making) on a single chip made by microfabrication methods. These chips exhibit combined properties of the two functions. The size of system has characteristic dimensions less than 1mm but more than 1mm. The configuration of these components determine the final deliverables of the switch. MEMS can be designed to meet user requirements on any level from microbiological application such as biomedical transducers or tissue engineering, to mechanical systems such as microfluidic diagnoses or chemical fuel cells. The low cost, small mass and minimal power consumption of the MEMS makes it possible to readily integrate to any kind of system in any environment. MEMS are faster, better and cheaper. They offer excellent electrical performances. MEMS working at Radio frequencies are RF MEMS. RF-MEMS switches find huge market in the modern telecommunication networks, biological, automobiles, satellites and defense systems because of their lower power consumptions at relatively higher frequencies and better electrical performances. But the reliability is the major hurdle in the fate of RF MEMS switches. Reliability mainly arises due to the presence of residual stresses, charging current, fatigue and creep and contact degradation. The presence of residual stresses in switches the S-Parameters of the switches are affected badly and the residual stress affects the final planarity of the fabricated structure. Design and simulation of an RF-MEMS switch is proposed considering the residual stresses in both on and off state. The operating frequency band is being optimized and the best possible feasible fabrication technique for the proposed switch design is being analyzed. S-Parameters are calculated and a comparison for the switches with stress and without stress is performed in FEM based HFSS software.
Keywords: RF-MEMS; Residual Stresses; Coplanar waveguide; Skin depth; Return loss; Insertion loss; Isolation; Reliability; Transmission coefficient; Reflection coefficient